2013
DOI: 10.1037/a0032090
|View full text |Cite
|
Sign up to set email alerts
|

Relationship and task conflict at work: Interactive short-term effects on angry mood and somatic complaints.

Abstract: Our research examined short-term within-person effects of relationship and task conflict on angry mood and somatic complaints. We assumed that conflicts of both kinds would be prospectively related to both indicators of impaired well-being, that the effect of relationship conflict would be stronger than the effect of task conflict, and that the effect of relationship conflict would be stronger when task conflict is low than when it is high. We tested our hypotheses with a daily diary study with ratings made 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 94 publications
(136 reference statements)
10
102
0
Order By: Relevance
“…Additionally, Oliver et al (2010) found in a longitudinal study that NA predicts work stressors over time, but work stressors do not predict NA over time. Finally, interpersonal conflict at work has been associated with both negative affective reactions in diary studies (Ilies et al, 2011;Meier et al, 2013) and with psychophysical strain in longitudinal studies (Falco et al, 2013b;Nixon et al, 2011). Overall, although more research is needed in order to examine the relationship between NA, ICW, and pro-inflammatory cytokines, the complete mediation model seems therefore consistent with current theories and evidence.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Additionally, Oliver et al (2010) found in a longitudinal study that NA predicts work stressors over time, but work stressors do not predict NA over time. Finally, interpersonal conflict at work has been associated with both negative affective reactions in diary studies (Ilies et al, 2011;Meier et al, 2013) and with psychophysical strain in longitudinal studies (Falco et al, 2013b;Nixon et al, 2011). Overall, although more research is needed in order to examine the relationship between NA, ICW, and pro-inflammatory cytokines, the complete mediation model seems therefore consistent with current theories and evidence.…”
Section: Discussionsupporting
confidence: 70%
“…Managers and supervisors should prevent ICW by creating a climate of trust and cooperation, in which employees can disagree about the content of the task being performed (i.e., task conflict) without disagreement over personal issues that are not task-related (i.e., relationship conflict; Meier et al, 2013). Indeed, task conflict may have less negative consequences on a worker's well-being than relationship conflict (Meier et al, 2013). In this perspective, once people disagree, supervisors may promote confrontation aimed at resolving a specific problem and discourage attacks related to the person.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of the assumption of both misattribution processes and inadequate behaviors, research has found task conflicts to foster negative emotionality, which in turn engenders relationship conflicts (Meier, Gross, Spector, & Semmer, 2013;Rispens, 2012).…”
Section: The Association Between Task and Relationship Conflictsmentioning
confidence: 99%
“…Group projects, like creating an advertisement for an item usually suffers from such conflicts, as one is dependent on the creative team for the main design and layout, the photographer for the visual effects and so on and so forth. Lack of efficiency in one sector holds the potential to disrupt the entire workflow into conflicts (Meier et al, 2013).…”
Section: Dependency Issuesmentioning
confidence: 99%